2011
DOI: 10.1371/journal.pone.0018644
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Sequencing Supply an Effective Way to Screen RNAi Targets in Large Scale for Potential Application in Pest Insect Control

Abstract: The key of RNAi approach success for potential insect pest control is mainly dependent on careful target selection and a convenient delivery system. We adopted second-generation sequencing technology to screen RNAi targets. Illumina's RNA-seq and digital gene expression tag profile (DGE-tag) technologies were used to screen optimal RNAi targets from Ostrinia furnalalis. Total 14690 stage specific genes were obtained which can be considered as potential targets, and 47 were confirmed by qRT-PCR. Ten larval stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 44 publications
3
137
0
10
Order By: Relevance
“…Much research is currently focusing on uncovering the molecular and physiological mechanisms governing cellular uptake and spread of dsRNA, as well as function of the RNAi machinery [2][3][4][5][82][83][84]. Novel methods for target gene selection [2,85,86], improved dsRNA construct designs [4,8], transfection reagents [4,5,64], and stabilityenhancing technologies such as chitosan/dsRNA nanoparticles [64,79] are being used to enhance RNAi efficiency in many species. Together, these efforts and numerous other toxicology studies utilizing RNAi, many of which are described in this review, are advancing the development of new RNAi-based tools for better management of insect pests.…”
Section: Resultsmentioning
confidence: 99%
“…Much research is currently focusing on uncovering the molecular and physiological mechanisms governing cellular uptake and spread of dsRNA, as well as function of the RNAi machinery [2][3][4][5][82][83][84]. Novel methods for target gene selection [2,85,86], improved dsRNA construct designs [4,8], transfection reagents [4,5,64], and stabilityenhancing technologies such as chitosan/dsRNA nanoparticles [64,79] are being used to enhance RNAi efficiency in many species. Together, these efforts and numerous other toxicology studies utilizing RNAi, many of which are described in this review, are advancing the development of new RNAi-based tools for better management of insect pests.…”
Section: Resultsmentioning
confidence: 99%
“…We nevertheless cannot preclude the possibility that dsRNAs and siRNAs could also enter into larval tissues via other routes such as across the unsclerotized and untanned cuticle shortly after hatching from the egg or by infiltration of the tracheal system. Consistent with this idea, an earlier study showed that dsRNA can induce an RNAi effect when sprayed onto larvae of another lepidopteran species, the Asian corn borer Ostrinia furnacalis (Guenée) (Wang et al, 2011).…”
Section: Tablementioning
confidence: 65%
“…76 Microinjection of dsRNAs against actin, chitin synthase 1 and V-ATPase in the citrus mealybug, Planococcus citri, showed that the corresponding mRNAs are good targets for RNAi. 50 In addition to microinjection, RNAi effects have also been achieved by soaking (C. elegans), 77 spraying (Ostrinia furnalalis), 78 and electroporation (Ixodes scapularis) 79 approaches to deliver RNAi inducers. In a recent study, El-Shesheny, et.…”
Section: 65mentioning
confidence: 99%